Pengaruh model C.I.R.C berbantuan media komik literasi terhadap kemampuan membaca pemahaman siswa kelas III di SD Negeri Wirogomo 01 - Dariyanto, Alfin; Purwanti, Kartika Yuni (Universitas Sarjanawiyata Tamansiswa, 2025)
Reading is a complex skill that involves a series of other smaller skills. The aim of this research is to determine the differences and influences on students' reading comprehension abilities through the use of the CIRC model assisted by comic literacy at SD N Wirogomo 01. The experimental research design that will be used in this research is the Quasy Experiment Design with the type The One Group Pretest-Posttest Design. The sample in this study was all class III students at SD Negeri Wirogomo 01 totaling 30 and SD Wirogomo 02 totaling 22 students. The results of the research show that there is a difference between students' reading abilities assisted by the CIRC model assisted by comics at SD Wirogomo 01. The results of the unstandardized coefficient are 7.232, that if there is comic media (x) then the reading comprehension consistency value (y) is 7.232. The regression coefficient figure is 0.385. This figure means that for every 1% addition of comic media (x), reading comprehension (y) will increase by 0.385. It can be concluded that HO is rejected and Ha is accepted, which means that there is an influence between the CIRC model assisted by comics on the reading comprehension of class III students. Wirogomo 01 Elementary School.